2019
DOI: 10.1002/stc.2317
|View full text |Cite
|
Sign up to set email alerts
|

Computational modeling of a unique tower in Kuwait for structural health monitoring: Numerical investigations

Abstract: Summary Computational modeling, in addition to data analytics, plays an important role in structural health monitoring (SHM). The high‐fidelity computational model based on the design and construction information provide important dynamics information of the structure and, more importantly, can be updated against field measurements for SHM purposes such as damage detection, response prediction, and reliability assessment. In this paper, we present a unique skyscraper (Al‐Hamra Tower) located in Kuwait City and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…Sun et al [29] demonstrated a skyscraper building model, namely, the Al Harma Tower in Kuwait, which is approximately 413 m in height with 86 floors, using E-tabs together with a building with two curved shear walls to the combined height of the buildings by applying three methods: system identification, interferometry-based wave propagation analysis, and wave-based damage detection. The building underwent large deformations due to heavy dead load and seismic response.…”
Section: Strategies Of Damage Detection In Buildings Using Shmmentioning
confidence: 99%
“…Sun et al [29] demonstrated a skyscraper building model, namely, the Al Harma Tower in Kuwait, which is approximately 413 m in height with 86 floors, using E-tabs together with a building with two curved shear walls to the combined height of the buildings by applying three methods: system identification, interferometry-based wave propagation analysis, and wave-based damage detection. The building underwent large deformations due to heavy dead load and seismic response.…”
Section: Strategies Of Damage Detection In Buildings Using Shmmentioning
confidence: 99%
“…Therefore, the FE model updating with a certain algorithm is necessary to make the FE model to best represent the real structures by using the field or laboratory measurement data from the prototype or the physical scale structure. Note that SHM systems are installed on many long‐span cable‐stayed bridges and other large and complex structures to monitor their behavior, and they can acquire detailed information on the loading conditions, global and local structural responses, and damage status of these structures. Thereby, they can provide valuable measurement data for updating the sensitive but uncertain parameters in the FE model to achieve high‐fidelity representation.…”
Section: Introductionmentioning
confidence: 99%
“…However, the FE model constructed based on design drawings can hardly reflect the actual state of a longspan bridge after experiencing a moderate or strong earthquake. It is worth noting that the recently developed structural health monitoring (SHM) system, [3][4][5][6][7] which has been installed in many engineering structures including long-span bridges, can provide the real-time measurement data of structural responses. How to use the real-time measured nonlinear structural responses to update the FE model and make it capable of best representing the real damaged structures becomes necessary.…”
Section: Introductionmentioning
confidence: 99%